PROFIL PENGETAHUAN DAN PERSPEKTIF HIPNOTERAPI DI KALANGAN MASYARAKAT WILAYAH SURABAYA - Fauziyyah Syandria Afrisa; Amara Damayanti; Mutmainnah Mutmainnah; Shabrina Insan Nabil; Luthfia Andini Nathaneila; Febri Zalfa’ Pratama; Avif Muhammad Zaki Hidayat; Reza Fahlevy Firmansyah Putra; Alwiyah Alwiyah; Abdul Rahem (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Hypnotherapy is an alternative and complementary therapy or non-pharmacological therapy that uses hypnosis as a suggestion of the human unconscious. Many people are negative about hypnotherapy and do not know that it has many benefits. The purpose of this study is expected to increase knowledge and change people's perspectives on hypnotherapy treatment. This study is a cross sectional study with non-random sampling (accidental sampling) techniques with research instruments in the form of online questionnaires and spread leaflets. The study was 108 respondents, with 108 respondents meeting the inclusion criteria. The results of the knowledge study showed 38.0% with good knowledge, 46.3% of respondents with sufficient knowledge and 15.7% of respondents with low knowledge and results at perspective showed 18% of respondents were positive, and 82% were negative. Based on the results of the respondents' knowledge and perspective, there is a need for an introduction to hypnotherapy treatment to prevent misperception among the people of Surabaya.